2016
DOI: 10.4049/jimmunol.1600697
|View full text |Cite
|
Sign up to set email alerts
|

DNA Prime-Boost Vaccine Regimen To Increase Breadth, Magnitude, and Cytotoxicity of the Cellular Immune Responses to Subdominant Gag Epitopes of Simian Immunodeficiency Virus and HIV

Abstract: HIV sequence diversity and the propensity of eliciting immunodominant responses targeting variable regions of the HIV proteome are hurdles in the development of an effective AIDS vaccine. An HIV-derived conserved element (CE) p24gag plasmid DNA (pDNA) vaccine is able to redirect immunodominant responses to otherwise subdominant and often more vulnerable viral targets. By homology to the HIV immunogen, seven CE were identified in SIV p27Gag. Analysis of 31 rhesus macaques vaccinated with full-length SIV gag pDN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
74
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 36 publications
(81 citation statements)
references
References 58 publications
7
74
0
Order By: Relevance
“…After priming, the IM delivered vaccine induced robust Gag CE-specific (Figure 2A, top left panel) and Env CE-specific (Figure 2C, top left panel) T cell responses in all animals, as we previously reported, 76 , 77 reaching up to 1.2% of circulating total Gag and Env CE T lymphocytes in macaque T152. The ID delivered vaccine induced much lower CE-specific T cell responses and were detected in only 5 of the 8 animals (Figure 2A and 2C, top middle panels).…”
Section: Resultssupporting
confidence: 82%
See 4 more Smart Citations
“…After priming, the IM delivered vaccine induced robust Gag CE-specific (Figure 2A, top left panel) and Env CE-specific (Figure 2C, top left panel) T cell responses in all animals, as we previously reported, 76 , 77 reaching up to 1.2% of circulating total Gag and Env CE T lymphocytes in macaque T152. The ID delivered vaccine induced much lower CE-specific T cell responses and were detected in only 5 of the 8 animals (Figure 2A and 2C, top middle panels).…”
Section: Resultssupporting
confidence: 82%
“…We previously reported the generation of two DNA vaccines targeting the highly conserved sequences in HIV Gag 20 , 21 , 73 (and its homolog SIV p27CE) 76 and in HIV Env (Env CE) 77 ( Figure 1 A) and demonstrated induction of robust CE-specific T cell responses in cohorts of vaccinated macaques. The CE selection included analysis of MHC binding prediction to address immunogenicity in humans, and we found that epitopes from all MHC class I known supertypes were represented in Gag CE.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations